2018
DOI: 10.2174/1874325001812010514
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biplane Double Supported Screw Fixation For Fracture Neck Femur In Elderly Population: A Prospective Study

Abstract: Introduction: The treatment of fracture neck femur varies according to the age of patient, the displacement of fracture fragments and the duration of the fracture. Various treatment options available for elderly are screw fixation, hemiarthroplasty and total hip arthroplasty. Materials and Methods: This is a prospective study done at authors institutes between January 2014- December 2016. 30 patients aged more than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Moreover, due to the biplane placement, enough space for a third screw is provided, whereas in the conventional methods for fixing neck femur, only one or a maximum of two screws can be placed at an obtuse angle. 18 Regarding demographic characteristics, the age of the patients ranges from 51 to 72 years, 65% of patients were males, and in accordance with our results, the study of Kalia et al 19 There seems to be a lot of controversy regarding the cannulated screw fixation for fracture neck femur like the number of screws to be used, configuration of screws and their position in head and neck. The method most widely practiced by surgeons for fixing the fracture neck femur is by three cancellous screws placed parallel to each other and various authors have reported the failure rate to be as high as 20-42%.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, due to the biplane placement, enough space for a third screw is provided, whereas in the conventional methods for fixing neck femur, only one or a maximum of two screws can be placed at an obtuse angle. 18 Regarding demographic characteristics, the age of the patients ranges from 51 to 72 years, 65% of patients were males, and in accordance with our results, the study of Kalia et al 19 There seems to be a lot of controversy regarding the cannulated screw fixation for fracture neck femur like the number of screws to be used, configuration of screws and their position in head and neck. The method most widely practiced by surgeons for fixing the fracture neck femur is by three cancellous screws placed parallel to each other and various authors have reported the failure rate to be as high as 20-42%.…”
Section: Discussionsupporting
confidence: 88%
“…The middle and proximal screws are inserted first followed by the distal screw as they are perpendicular to the fracture surface. (Figure 7) [31,32].…”
Section: Fully Threaded Screwmentioning
confidence: 99%